Antenna Array Design by Artificial Bee Colony Algorithm With Similarity Induced Search Method - Wang, Lei; Zhang, Xin; Zhang, Xiu (IEEE transactions on magnetics, 2019)
Antenna array has been extensively applied to wireless communication systems. Optimal design of antenna array is very useful to attain desired spatial beam and reduce signal degradation. Potential search directions in artificial bee colony (ABC) algorithm are mixed with both large step size and small step size. This could lead to the malfunction of employed bee stage and onlooker bee stage of ABC algorithm. This paper proposes to improve the effectiveness of ABC by a similarity induced search method. This method adaptively adjusts search step size. Employed bees perform large step size search, while onlooker bees do small step size search. Scout bees could probe potential high-quality solutions in neighborhoods. The proposed algorithm is tested on antenna array design problem. Compared with four other algorithms, the results verify the effectiveness of the proposed algorithm. Furthermore, the scalability of the proposed algorithm is also analyzed in terms of array element and computational time. Scalability analysis also shows that the proposed algorithm is suitable for solving antenna array design problems.